2018
DOI: 10.1016/j.rbms.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative economic study of the use of corifollitropin alfa and daily rFSH for controlled ovarian stimulation in older patients: Cost-minimization analysis based on the PURSUE study

Abstract: This study presents an economic assessment of controlled ovarian stimulation in assisted reproductive technology procedures in Spain, comparing the use of corifollitropin alfa and various forms of recombinant follicle-stimulating hormone (rFSH) in women of advanced maternal age. A cost-minimization analysis (CMA) was performed to assess the cost per cycle of controlled controlled ovarian stimulation, including only direct costs associated with the stimulation phase. The CMA was based on the population characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
0
9
0
2
Order By: Relevance
“…The most recent and direct evidence comes from the PURSUE study (15), in which a single SC injection of 150 mg of corifollitropin alfa was equivalent to daily administration of 300 IU of rFSH in a trial involving 1,390 women ages 35-42. An economic analysis based on the PURSUE study showed that, in Spain, COS with corifollitropin alfa is less expensive than daily doses of rFSH whenever it exceeds 250 IU per day (21). In fact, more than 250 IU are usually required for women ages 35-42 years, who make up the majority of infertile patients seeking ART (22).…”
Section: Discussionmentioning
confidence: 99%
“…The most recent and direct evidence comes from the PURSUE study (15), in which a single SC injection of 150 mg of corifollitropin alfa was equivalent to daily administration of 300 IU of rFSH in a trial involving 1,390 women ages 35-42. An economic analysis based on the PURSUE study showed that, in Spain, COS with corifollitropin alfa is less expensive than daily doses of rFSH whenever it exceeds 250 IU per day (21). In fact, more than 250 IU are usually required for women ages 35-42 years, who make up the majority of infertile patients seeking ART (22).…”
Section: Discussionmentioning
confidence: 99%
“…(€13,726 versus €12,511, respectively) differs from a previous cost-minimization analysis (CMA) of the two approaches (Barrenetxea et al, 2018). In addition to a difference in design (CMA versus CEA), the other study was conducted in a different setting (Spain; a high-income country) and did not include direct non-medical and indirect cost data.…”
Section: Discussionmentioning
confidence: 99%
“…The cost per cycle of ovarian stimulation was determined based on data from the PURSUE study, which was conducted in Spain (a high-income country) and only included direct costs associated with the stimulation phase (Barrenetxea et al, 2018). However, the literature shows that there is currently great diversity in the IVF funding and reimbursement policies within Europe, the USA, Australia and New Zealand (Chambers et al, 2009(Chambers et al, , 2012Connolly et al, 2010), while patients in low-or middle-income countries have to self-fund infertility treatments (Dyer and Patel, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…На сегодняшний день пациентки, проходящие процедуру экстракорпорального оплодотворения (ЭКО) в центрах ВРТ, находятся в возрасте старше 30 лет (преимущественно в возрасте 30-37 лет) [3]. С учетом того, что у женщин естественное снижение фертильности начинается после 35 лет, а возможность рождения ребенка завершается примерно за 10 лет до наступления менопаузы [4], которая в среднем наступает в 51 год, данная тенденция может быть ассоциирована с проблематичностью проведения протоколов ВРТ.…”
unclassified
“…Кроме того, G. Barrenetxea и соавт. [3] в 2018 г. в исследовании PURSUE показали, что применение пролонгированного гонадотропина у Corifollitropin alfa for ovarian stimulation in in vitro fertilization in women of advanced maternal age женщин старшего репродуктивного возраста на 20% снижает стоимость лечения по сравнению с ежедневным применением р-ФСГ.…”
unclassified